Guidelines to Develop Students of Fashion Show Major - Liu , Wenxin (International Journal of Sociologies and Anthropologies Science Reviews, 2025)
Background and Aim: The costume show is a beautiful business. In the countless spotlights, in the center of the stage and people's eyes focused, the light turns around, showing beautiful posture and clothes, this is a lot of people dream of the scene. In 1977, 30 years after Pierre Cardin led foreign models to China, China's textile and apparel-related institutions of higher learning, continued to set up the "clothing performance" major, in the late 1990s, the training level gradually increased to colleges and universities. At present, China has hundreds of universities with this specialty. The specialty of costume performance has a history of more than 20 years in China, but it is still in the embryonic stage in terms of the guidelines to develop for training students in costume performance. Therefore, it is particularly important to develop accurate, reasonable and effective guidelines to develops for the fashion performance profession. Materials and Methods: Research relevant literature, make questionnaires, confirm the validity, and find out the current situation and problem factors. Draft guidelines to develop for training students majoring in fashion performance, and then set up focus groups to revise and supplement the drafted guidelines to develop. Finally, the experts are consulted to determine the final guidelines to develop for training students in costume performance. Results: In this study, the number of guidelines for training students majoring in fashion performance is summarized as follows: Physique 11, physical strength and health 8, movement 11, skill 9, emotion 4, and communication 4. Conclusion: The guidelines to develop this study can not only effectively improve students' Physique, physical fitness, health, movement, skill, emotion, and Communication, but also select a variety of different ways and different collocation ways to form new guidelines to develop for the six factors.